Characteristics of Bulletproof Vests Made from COPEFB Fiber: Implications on Mechanical, Electrical, and Physical Resistance - Nikmatin, Siti; Irmansyah, Irmansyah; Palupi, Endah Kinarya; Umam, Rofiqul (International Journal of Biomaterials, 2023)
This research aims to examine the characteristics of bulletproof vests from corncob oil palm empty fruit bunch (COPEFB) biocomposite, where mechanical, electrical, and physical resistance tests have been successfully conducted. The variations in the diameter of the twisted thread used to make the basic material for bulletproof vests include 1 mm, 3 mm, 6 mm, and 10 mm, which were tested for their mechanical, electrical, and physical properties. To identify which biocomposite is good at damping bullets, an impact and a firing test were carried out to determine the kinetic energy and the depth of the bullet, respectively. The results showed that the impact value improved with an increase in the diameter of the twisted yarn used. The largest and the lowest impact values were 1.157 kJ and 0.277 kJ on the epoxy sample with a twisted thread diameter of 10 mm and 1 mm, respectively. It was also discovered that the biocomposite samples made from 6 mm to 10 mm twisted threads were the best samples, impermeable to bullets. This was due to the excess natural fiber content which improved the flexibility and absorption of kinetic energy from the high rate of projectile bullets. According to the results of the firing test, some samples are translucent, while others cannot be penetrated by bullet projectiles. The projectile went inside, and the composite was damaged. All the high filler loading samples were translucent to bullets, while some of the low loading samples were translucent and impermeable to bullets. Based on these results, biocomposite samples made of 6 mm and 10 mm twisted yarn are the best samples that are impermeable to bullets.